The archaeology of slavery in early Medieval northern Europe : the invisible commodity - European Association of Archaeologists 2014 (2021)
This volume is the first comprehensive study of the material imprint of slavery in early medieval Europe. While written sources attest to the ubiquity of slavery and slave trade in early medieval British Isles, Scandinavia and Slavic lands, it is still difficult to find material traces of this reality, other than the hundreds of thousands of Islamic coins paid in exchange for the northern European slaves. This volume offers the first structured reflection on how to bridge this gap. It reviews the types of material evidence that can be associated with the institution of slavery and the slave trade in early medieval northern Europe, from individual objects (such as e.g. shackles) to more comprehensive landscape approaches. The book is divided into four sections. The first presents the analytical tools developed in Africa and prehistoric Europe to identify and describe social phenomena associated with slavery and the slave trade. The following three section review the three main cultural zones of early medieval northern Europe: the British Isles, Scandinavia, and Slavic central Europe. The contributions offer methodological reflections on the concept of the archaeology of slavery. They emphasize that the material record, by its nature, admits multiple interpretations. More broadly, this book comes at a time when the history of slavery is being integrated into academic syllabi in most western countries. The collection of studies contributes to a more nuanced perspective on this important and controversial topic. This volume appeals to multiple audiences interested in comparative and global studies of slavery, and will constitute the point of reference for future debates.